2022
DOI: 10.1007/s10803-022-05789-4
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Neurodevelopmental Trajectories in Groups of Very Preterm Children Screening Positively for Autism Spectrum Conditions

Abstract: Very preterm (VPT; < 33 weeks’ gestation) toddlers screening positively for autism spectrum conditions (ASC) may display heterogenous neurodevelopmental trajectories. Here we studied neonatal brain volumes and childhood ASC traits evaluated with the Social Responsiveness Scale (SRS-2) in VPT-born toddlers (N = 371; median age 20.17 months) sub-divided into three groups based on their Modified-Checklist for Autism in Toddlers scores. These were: those screening positively failing at least 2 critical items (c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 58 publications
(80 reference statements)
0
3
0
Order By: Relevance
“…Our findings further support the concept of equifinality (Cicchetti and Rogosch, 1996), recognizing the possible existence of multiple pathways associated with specific outcomes. We have in fact recently shown that only a subgroup of VPT children exhibiting high ASC traits displayed neonatal cerebellar alterations, suggesting distinct aetiological trajectories associated with ASC outcomes (Hadaya et al, 2022). This study, and in particular our results highlighting the centrality of executive function and behavioral problems in driving other difficulties in VPT children, further strengthens the argument in favor of person-based treatment approaches targeting underlying behaviors and difficulties rather than surface level symptoms (Kasari et al, 2014).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Our findings further support the concept of equifinality (Cicchetti and Rogosch, 1996), recognizing the possible existence of multiple pathways associated with specific outcomes. We have in fact recently shown that only a subgroup of VPT children exhibiting high ASC traits displayed neonatal cerebellar alterations, suggesting distinct aetiological trajectories associated with ASC outcomes (Hadaya et al, 2022). This study, and in particular our results highlighting the centrality of executive function and behavioral problems in driving other difficulties in VPT children, further strengthens the argument in favor of person-based treatment approaches targeting underlying behaviors and difficulties rather than surface level symptoms (Kasari et al, 2014).…”
Section: Discussionsupporting
confidence: 77%
“…Very preterm participants, born before 32 completed weeks of gestation, were recruited as new-borns between 2010 and 2013 as part of the Evaluation of Preterm Imaging study (ePrime; EudraCT 2009-011602-42;Edwards et al, 2018), from hospitals within the North and Southwest London Perinatal Networks and were followed up behaviorally throughout childhood (Kanel et al, 2021a;Hadaya et al, 2022). The current study focuses on behavioral assessments conducted at a median age of 8.75 years (n = 148).…”
Section: Participantsmentioning
confidence: 99%
“…A dimensional approach to understanding psychopathology fits with the concept of equifinality (Cicchetti and Rogosch, 1996), recognising the possible existence of multiple pathways associated with specific outcomes. We have in fact recently shown that only a subgroup of VPT children exhibiting high ASC traits displayed neonatal cerebellar alterations, suggesting distinct aetiological trajectories associated with ASC outcomes (Hadaya et al, 2022). This study, and in particular our results revealing the centrality of executive function and behavioural problems in driving other difficulties for VPT children, further strengthens the argument in favour of person-based treatment approaches targeting underlying behaviours and difficulties rather than surface level symptoms (Kasari et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…VPT participants, born before 32 completed weeks of gestation, were recruited as new-borns between 2010 and 2013 as part of the Evaluation of Preterm Imaging study (ePrime; EudraCT 2009-011602-42; Edwards et al, 2018), from hospitals within the North and Southwest London Perinatal Networks and were followed up behaviourally throughout childhood (Hadaya et al, 2022; Kanel et al, 2021). The current study focuses on behavioural assessments conducted at a median age of 8.75 years (n=148).…”
Section: Methodsmentioning
confidence: 99%
“…Disturbances manifest in increased sleep latency ( Martínez-Cayuelas et al, 2022 ), reduced REM sleep time ( Buckley et al, 2010 ) and parental report of worse sleep quality ( Anders et al, 2011 ; MacDuffie et al, 2020 ), resulting in substantial consequences on daytime functioning ( Anders et al, 2012 ). Developmental trajectories may also be influenced by genetic etiology or the timing of birth, highlighting the complex pathophysiology ( Heavner and Smith, 2020 ; Hadaya et al, 2022 ). Thus, disrupting sleep at different timepoints in development or rodent models may align with different aspects of the progression of these disorders.…”
Section: Behavioral Consequences Of Developmental Sleep Disruptionmentioning
confidence: 99%